Good half gone eaudiobook - Fisher, Tarryn (Harlequin Audio, 2024)
"The ending shattered me in a way only Tarryn Fisher can!" —Colleen Hoover From the #1 New York Times bestselling author of Never Never Iris Walsh saw her twin sister get kidnapped—so why does no one believe her? Iris narrowly escaped her twin sister's fate as a teen: abducted in broad daylight and long gone before she could convince the cops there was anything to investigate. With Piper presumed a runaway and no evidence to go on but Iris's scattered memories, the case quickly goes cold. Ever since that terrible day, Iris' search for Piper has bordered on obsession. Chasing leads across years and following clues that all seem to point to a single name, Iris does everything she can to get close to the only person who might know the answer to the question that still haunts her: where did Piper go? And if the police still won't help, she'll just have to find the answer herself—using her criminal psychology degree to intern at the isolated psychiatric hospital on Shoal Island, where secrets lurk in the shadows and are kept under lock and key. But Iris soon realizes that something even more sinister is simmering beneath the surface of the Shoal, and that the patients aren't the only ones being observed... Looking for more captivating reads by Tarryn Fisher? Don't miss: Never Never The Wives The Wrong Family An Honest Lie